The multiplicity distribution of Kepler's exoplanets. Issue 3 (23rd August 2019) - Sandford, Emily; Kipping, David; Collins, Michael
Abstract: The true multiplicity distribution of transiting planet systems is obscured by strong observational biases, leading low-multiplicity systems to be overrepresented in the observed sample. Using the Kepler FGK planet hosts, we employ approximate Bayesian computation to infer the multiplicity distribution by comparing simulated catalogues to the observed one. After comparing a total of 10 different multiplicity distributions, half of which were two-population models, to the observed data, we find that a single-population model following a Zipfian distribution is able to explain the Kepler data as well as any of the dichotomous models we test. Our work provides another example of a way to explain the observed Kepler multiplicities without invoking a dichotomous planet population. Using our preferred Zipfian model, we estimate that an additional 2393_-717^+904 planets likely reside in the 1537 FGK Kepler systems studied in this work, which would increase the planet count by a factor of 2.22_-0.36^+0.46 . Of these hidden worlds, 663_-151^+158 are expected to reside in ostensibly single transiting planet systems, meaning that an additional planet(s) is expected for approximately 1-in-2 such Kepler systems.